LANGUAGE AND POWER IN DISCOURSE ANALYSIS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
Abstract: This article explores the intricate relationship between language and power through the lens of discourse analysis, a critical approach in sociolinguistics that examines how language shapes and is shaped by social hierarchies. Language is not a neutral tool but an instrument through which power is exercised, reinforced, and challenged in various social contexts, including politics, media, gender, and race. Discourse constructs reality, reflects societal norms, and perpetuates ideologies that maintain dominant power structures. Drawing on key theories from scholars like Foucault and Gramsci, the essay highlights how language serves to legitimize authority, control knowledge, and enforce social control, while also offering a means of resistance for marginalized groups. Аннотация: Эта статья исследует сложную взаимосвязь между языком и властью через призму дискурсного анализа — критического подхода в социолингвистике, который изучает, как язык формирует и формируется социальными иерархиями. Язык не является нейтральным инструментом, а служит средством, через которое власть осуществляется, укрепляется и оспаривается в различных социальных контекстах, включая политику, медиа, гендер и расу. Дискурс конструирует реальность, отражает общественные нормы и воспроизводит идеологии, поддерживающие доминирующие властные структуры. Опираясь на ключевые теории таких ученых, как Фуко и Грамши, статья подчеркивает, как язык служит легитимации власти, контролю над знаниями и социальной регуляции, а также предоставляет средство сопротивления для маргинализованных групп.